A colaboração premiada e a renúncia a direitos fundamentais sob as óticas do Estado e do colaborador - Dezan, Willy Potrich da Silva (2019)
Talk about renunciation implies abandoning the paternalistic idea that fundamental rights are inalienable, under penalty of transforming the rights of freedom into duties that curtail self-determination. Although there are several examples of ordinary renunciations of fundamental rights, the institute of state`s evidence reveals nuances that make its study, in this light, somewhat more complex. The resignation carried out by the collaborator is not exhausted in the dimension of not exercising one or several fundamental rights but goes further and creates for the State an area of freedom of action that did not exist before, precisely because of the mitigated fundamental right norm. Therefore, while on the one hand it is possible to affirm the renunciation of fundamental rights as a form of exercise of the fundamental right itself, which may prove to be more advantageous for the individual in the particular case, on the other hand one can not ignore the consequences that may result from this act of renunciation, capable of creating real restrictions to fundamental rights, which require the observance of some assumptions and requirements for its validity. This complexity not only gives rise to several criticisms that are directed to the institute of the state`s evidence, but also dictates the tone of the present work when analyzing the fundamental rights related to the institute and the concrete possibility of its resignation and restriction. In the end, the response leads to the reaffirmation of state`s evidence as an essential instrument in the exercise of the State's duty to protect from the challenges created by new forms of crime, but not without some relevant criticism of the way in which forensic practice has been trying to redesign the institute and to walk with broad steps towards a dangerous expansion of the spaces of consensus in criminal proceedings.